2006
DOI: 10.1523/jneurosci.3691-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanics of Coordination during Swallowing inAplysia californica

Abstract: Bernstein (1967) hypothesized that preparation of the periphery was crucial for correct responses to motor output. To test this hypothesis in a behaving animal, we examined the roles of two identified motor neurons, B7 and B8, which contribute to feeding behavior in the marine mollusk Aplysia californica. Neuron B7 innervates a hinge muscle and has no overt behavioral effect during smaller-amplitude (type A) swallows, because the hinge muscle is too short to exert force. Neuron B8 activates a muscle (I4) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 52 publications
0
48
0
Order By: Relevance
“…It is clear that many bites and many swallows occupy distinct locations in the space defined by their motor components, but it is also clear that there is some overlap. This is not surprising, because we have previously shown that swallows may have variants with different strengths of protraction, making them more similar to bites (Ye et al 2006a).…”
Section: What Variations In the Motor Program Affect Motor Behavior?mentioning
confidence: 71%
See 3 more Smart Citations
“…It is clear that many bites and many swallows occupy distinct locations in the space defined by their motor components, but it is also clear that there is some overlap. This is not surprising, because we have previously shown that swallows may have variants with different strengths of protraction, making them more similar to bites (Ye et al 2006a).…”
Section: What Variations In the Motor Program Affect Motor Behavior?mentioning
confidence: 71%
“…To characterize the key motor features, we determined the start and stop times of the I2 EMG during the protraction phase by measuring both the time of the first spike and the time at which the muscle EMG reached 10 Hz and the stop time when it fell below 5 Hz (Hurwitz et al 1996; 3 measures), the start and stop times of the largest units on RN (corresponding to activity in the B8a/b neurons; Chiel 1993a, 1993b; 2 measures), the start and stop times of the B4/B5 units on BN3 [largest units on BN3 (Warman and Chiel 1995) from the first to the last spike; 2 measures], and the start and stop times of identified motor neurons B6/B9 and B43 (Lu et al 2013;4 measures). Finally, we measured the third-largest units on BN2 (Church and Lloyd 1994;Morton and Chiel 1993b;Ye et al 2006a), focusing on when they began in retraction (1 measure), for a total of 12 different measures of the motor program. The start and end times of other features of the motor pattern that were absent in many motor patterns were noted but were not used further for the analysis in this report: activity in motor neuron B3 (largest extracellular unit on BN2), bursts of activity in B4/B5 above 40 Hz, the third largest unit on BN2 in the protraction phase, activity of motor neuron B38 in protraction, and activity of motor neuron B38 in retraction.…”
Section: Recording Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Multifunctionality is difficult to study, because it is hard to simultaneously characterize biomechanics and neural control. Because we established many of the neural and biomechanical mechanisms that underlie swallowing responses of different amplitude in the marine mollusk Aplysia californica (Ye et al, 2006), we sought to determine how these properties changed during a qualitatively different behavior, rejection. Magnetic resonance (MR) imaging showed that the central grasper (radula/odontophore) changes shape from spherical when it is open to ellispsoidal when it is closed (Neustadter et al, 2002b;Novakovic et al, 2006).…”
Section: Introductionmentioning
confidence: 99%